THE PRINCIPLES OF PUBLIC-UTILITY DEPRECIATION. - Preinriech, Gabriel A. D. (The Accounting Review, 1938)
Abstract Professor Perry Mason's monograph on the "Principles of Utility Depreciation" with great interest and consider it as valuable a contribution to the literature of accountancy and public utility regulation as can be made by the traditional discursive method of presentation and by what is still essentially a "single machine" approach. Unfortunately, the subject is far too complex for these limitations. To give its students a bird's-eye view of the main problem unobscured by innumerable conflicting opinions, decision, rulings, etc., it is necessary to make, first of all, an introductory comparison of representative methods of depreciation, as applied to a composite plant consisting of many similar items of equipment which are continuously replaced. After demonstrating, how the "rate" chargeable to the consumer is determined by the method in various circumstances, it is in order to investigate the theoretical requirements, which the "true" method must fulfil. Finally, the enormous practical difficulties may be pointed out and compromises discussed.